Thrombotic Conditions in Patients with COVID-19: Dynamics of D-Dimer and Tactics of Anticoagulant Therapy - Nykonenko, Andriy O.; Podluzhniy, Heorhii S.; Koliada, Nadia A.; Levchak, Yuriy A.; Hardubey, Yevheniy Yu.; Zubryk, Iryna V.; Naumova, Olga O.; Nykonenko, Olexandr S.; Horlenko, Fedir V.; Matvieiev, Serhii O.; Riabokon, Olena V. (Ukrainian Journal of Cardiovascular Surgery, 2022)
In patients with COVID-19, histological examination of the pulmonary vessels shows serious disorders (local thrombosis and microangiopathy), significantly different to those in the control group composed of patients with influenza. Some studies have shown that coronavirus enters cells by binding angiotensin-converting enzyme 2 which is found mainly on the alveolar epithelium and endothelium. The increase in D-dimer levels is typical for patients with COVID-19. Although many inflammatory processes can affect D-dimer levels, an increase in D-dimer during COVID-19 is more likely to indicate thrombosis. The aim. To analyze the patients who have suffered from COVID-19 and to determine possible risk factors for the development of thrombotic complications and define the surgical or medical therapy tactics. Material and methods. The study was conducted from October 2020 to April 2021 in Ukraine (Zaporizhzhia, Uzhhorod, Kherson and Kyiv). We analyzed 121 patients aged 46.9± 15.3 years, 64 (52.8%) men and 57 (47.1%) women. All the patients had positive PCR test for COVID-19. The changes in D-dimer were analyzed. Results. Forty-one (33.9%) patients had thrombotic complications. Pulmonary embolism (PE) was diagnosed in 14 patients, deep vein thrombosis (DVT) in 17, acute stroke in 2 and peripheral artery thrombosis in 8 cases. An increase in D-dimer level was observed in most patients and was not associated with clinical manifestations of thrombosis. At a D-dimer level of 11,000-10,564 ng/ml the patients had clinical symptoms of thrombotic condition which was confirmed by computed tomography or ultrasound examination. At an increase over 725-7000 ng/ml, there were no clinical signs of thrombosis. We performed standard medical therapy in patients with PE and DVT. In case of arterial thrombosis open surgery was performed in 4 patients and direct catheter thrombolysis in 1 case. Conclusion. In our opinion, anticoagulants should be prescribed for patients with a D-dimer level of more than 700 ng/ml. Full anticoagulation is prescribed for severe forms of COVID-19 or confirmed thrombosis. We didn’t find any correlation between the development of thrombotic complications in patients with COVID-19 and comorbidities, body mass index and other factors. Medical therapy was successful in all cases of PE and DVT, anticoagulants were prescribed for 1 year. Femoral artery thrombectomy was successfully performed in 4 patients. After direct catheter thrombolysis we got peripheral pulse. In all cases of arterial thrombosis, we prescribed anticoagulants for 2 months after discharge and acetylsalicylic acid for a long time.